An Examination of Asian and Pacific Islander LGBT Populations Across the United States : Intersections of Race and Sexuality - Battle, Juan; Pastrana, Jr., Antonio (Jay); Harris, Angelique (Palgrave Macmillan US : Imprint: Palgrave Pivot, 2017)
This book utilizes personal narratives and survey data from over 500 respondents to explore the diversity of experiences across Asian and Pacific Islander LGBT communities within the United States. Additionally, the authors document and celebrate many of the everyday strengths and strategies employed by this extraordinary population to navigate and negotiate their daily lives. Juan Battle is a Professor of Sociology at the Graduate Center, CUNY, USA Antonio (Jay) Pastrana, Jr. is an Associate Professor at John Jay College of Criminal Justice, CUNY, USA Angelique Harris is an Associate Professor of Sociology and Director of the Center for Gender and Sexualities Studies at Marquette University, USA.
Keywords: Social sciences.; Ethnology.; Sociology.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books